Inappropriate behavior and dropout from sport: A quantitative study of elite athletes in Denmark - Holum, M.; Diment, G. M.; Jakobsen, T. G.; Storm, R. K. (European Journal for Sport and Society, 2025)
In the international sporting arms race to win medals at major tournaments, addressing the determinants of elite athlete dropout is essential. This is especially true for smaller nations, which are at a disadvantage to large nations when it comes to the availability of talent. Therefore, the retention of the elite is essential. In this paper, we examine survey data from Danish top-level athletes to understand the factors that influence athletes' reflections on quitting. The study not only focuses on factors common to athlete dropout but includes the effect of inappropriate behaviour, bullying and harassment experienced by (some) athletes from their peers, coaches, or sport managers. Our findings suggest that athletes who feel safe and haven`t experienced transgressional behaviour from others are less likely to quit their elite sporting careers. Athletes from team sports are significantly less likely to consider quitting than athletes in individual sports. Also, the experience of inappropriate behaviour seems to have a significantly weaker effect on world-class athletes and elite athletes` plns on quitting. The results have implications for people supporting athletes in optimising their international competitiveness. A mentally and physically healthy supporting environment benefits the athletes and keeps them competing.